2014
DOI: 10.1177/0956462414544724
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the pattern of Kaposi’s sarcoma at Ocean Road Cancer Institute in Tanzania (2006–2011)

Abstract: Tanzania has high HIV and human herpes virus-8 rates linked to Kaposi’s sarcoma (KS). We conducted a study at the Ocean Road Cancer Institute (ORCI) in Dar es Salaam, Tanzania, to examine changes in proportions of KS to all cancers over the period (2006-2011) of increased AIDS management by ART. We included 1504 KS from ORCI and abstracted information regarding age, sex, HIV and TB, ART duration and KS lesions. Male KS patients (59.6%) were older (42.1±11.5 years) than females (40.4%) (36.2± 9.6 years). KS pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
1
20
1
Order By: Relevance
“…Unfortunately, unknown HIV status is a limitation that has been reported in previous studies and the results of this study should be taken with caution. 31,32 However, it is still important to report the results for this hospital-based study in order to further understand the HIV-positive cancer patients in this population and other similar underserved populations in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, unknown HIV status is a limitation that has been reported in previous studies and the results of this study should be taken with caution. 31,32 However, it is still important to report the results for this hospital-based study in order to further understand the HIV-positive cancer patients in this population and other similar underserved populations in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Uldrick et al, reported post-HIV seroprevalence of KSHV as very common in sub-Saharan Africa, with seropositivity rates above 50%; moderately prevalent in Mediterranean countries (20–30%), but much less common (< 10%) in most of Europe, Asia and the US [7]. In Tanzania, the prevalence of AIDS-related KS was reported to be 2.4% at Bugando medical center in northwestern Tanzania from 2004 to 2014 [8], whereas Koski et al , reported prevalence of AIDS-associated KS to have dropped from 10.1% in 2003 to 7.4% in 2011 in a study conducted at Ocean Road Cancer Institute (ORCI), Tanzania [9]. A study conducted from 2006 to 2007 at The Kilimanjaro Christian Medical Centre (KCMC) Regional Dermatology Training Center (RDTC) and Mawenzi Regional Hospital Infectious Diseases Clinic in Moshi, northern Tanzania, reported a 4% prevalence of KS [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical, prostate, breast, Kaposi sarcoma, and esophageal cancers are among the most common types of malignancies in Tanzania [24]. While cervical, prostate, and breast cancers account for large proportions of the cancer burden in this population, the proportion of Kaposi sarcoma, an AIDS-defining malignancy, to all other cancers diagnosed is decreasing [24, 25]. Although NADCs evaluated in this study decreased in percentage over the 12-year period, ongoing evolution of risk factors and population characteristics in Tanzania may lead to increasing proportions of these types of malignancies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This study of NADCs in patients presenting to ORCI has multiple strengths. This study builds upon work previously done in this population to analyze changing patterns of Kaposi’s sarcoma as well as work on three other NADCs in order to more broadly characterize changing cancer burden in Tanzania and contribute to knowledge for future research in this population [11, 25]. This large dataset of patients with lung, liver, and head and neck cancers contains cases that were pathologically confirmed and included individuals from a majority of Tanzania’s geographic regions.…”
Section: Discussionmentioning
confidence: 99%